C-ARM Guided Angiogram/Angioplasty for Selected Failed Arterio Venous Fistula. A Report of a Procedure at University Hospital of Nepal - Vaidya, S.; Karmacharya, R. M.; Singh, A. K.; Vaidya, P. R.; Malinowski, M.; Dhakal, A. (Kathmandu University Medical Journal, 2021)
End Stage Renal Disease is a last stage of Chronic Kidney Disease which is characterized by Glomerular Filtration rate of less than 15 ml/min/1.73 m2. Hemodialysis is the most commonly used modality for treatment of Chronic Kidney disease. Among the access for hemodialysis arteriovenous fistula is the most common modality. However most common problems of fistula are significant stenosis of more than 50% which is characterized by limb swelling, pigmentation, tortuous veins, and difficulty maintaining flow during dialysis from AV fistula. These can be managed either by minimal intervention or with surgical intervention. Very few hospitals in Nepal and other countries have an angiographic suite to perform minimal intervention include angiogram with angioplasty. So in this case we try to address the use of C-Arm to perform angiogram or fistulogram and even angioplasty for the management of significant stenosis or complications of arteriovenous fistula.